Analysis of Stakeholders' Perceptions of The Impact of Crisis on Tourism in Ogun State, Nigeria - Adesina-Uthman, Ganiyat Adejoke; Majebi, Enesi Chukwuemeka; Fagbolu , Olukemi Adedokun; Obaka, Abel Inabo (Jurnal Internasional Riset Bisnis Pariwisata, 2023)
Ogun State, Nigeria, is experiencing crises, including kidnapping and terrorism, that can impact its destinations. Thus, this study examined the perceptions of 133 tourists on the influence of these crises on their visitation to an attraction in the state, using a questionnaire survey. Two attraction officials were also interviewed on whether such crises impact revenue generation and employment. Results from the questionnaires, which were analyzed using PSPP frequency distribution, show that although terror crises had no significant influence on tourists' visitation to the attraction, they were concerned with the level of insecurity at the destination. Also, the transcribed interview outcomes reveal that, although similar crises had no significant impact on tourism, their perceptions can affect revenue generation and employment when destinations are poorly projected. Consequently, these findings suggest the need for improved safety measures and mechanisms for promoting safe places at the destination by the authorities, for improved tourist arrivals, revenue, and employment opportunities.